2006
DOI: 10.1163/156855406778440749
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial adhesion between semi-crystalline polymers (polypropylene and nylon-6): in situ compatibilized interface and fracture mechanism

Abstract: The interfacial fracture toughness between semi-crystalline polymers (polyamide/polypropylene) were studied to understand the failure mechanisms at the interface, especially when the interface was reinforced by an in situ compatibilizer. Based on the observation of the interface using scanning electron microscopy and wide angle X-ray spectroscopy, it was revealed that crystalline structure of polypropylene was not affected by the in situ compatibilizer at the interface. The reinforcing mechanism could be quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Crystallinity is known to affect interfacial adhesion, 33,34 and this could increase the adhesive force even with constant copolymer reaction rate. We compared the crystallinity of laminated and coextruded functional PE/ LLDPE-1 blends and found that crystallinity was affected little by processing: 8-9% (pellets) and $11% (coextrusion).…”
Section: Reaction Acceleration Through Coextrusionmentioning
confidence: 99%
“…Crystallinity is known to affect interfacial adhesion, 33,34 and this could increase the adhesive force even with constant copolymer reaction rate. We compared the crystallinity of laminated and coextruded functional PE/ LLDPE-1 blends and found that crystallinity was affected little by processing: 8-9% (pellets) and $11% (coextrusion).…”
Section: Reaction Acceleration Through Coextrusionmentioning
confidence: 99%
“…Although pressure changes the capture volume around a reactive group and accelerates reaction, the pressure dependence of the rate constant for typical liquid‐phase reactions is much too weak to alter the rate for the range of pressures encountered here . Crystallinity is known to affect interfacial adhesion, and this could increase adhesion even with constant copolymer reaction rate. We compared the crystallinity and crystal structures near the interface for coextrusion with different dies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nylon 6, also known as polyamide 6, has also attracted good attention in research due to its high mechanical properties and good oxygen transport resistance [1]. PP and nylon 6.6 blends have received much attention in the last decade due to their enhanced properties [2,3]. Te blend was selected to study the material contribution to the enhancement of the overall properties and alterations of the morphology of the blend.…”
Section: Introductionmentioning
confidence: 99%